The characteristics of copper containing SBA-15 prepared by impregnation and pH adjustment methods and their activities for N2O decomposition - Mohd Husin, Mohd Haizal; Dewayanto, Nugroho; Nordin, Mohd Ridzuan; Jinli, Li (American-Eurasian Network for Scientific Information, 2015)
Two types of Cu-SBA-15 catalysts were successfully prepared by impregnation and by pH adjustment methods. All synthesized materials have been characterized by XRD, Nitrogen adsorption–desorption, and TEM. After the impregnation of copper, the unit-cell, specific surface area and pore volume of SBA-15 were found to decrease, while the formation of CuO deposited on the framework was detected. On the contrary, the catalyst prepared by pH modification method indicated the increase of unit-cell, surface area, pore volume, and wall thickness after the incorporation of the copper ions on SBA-15 and copper atoms were substituted into the framework of the SBA-15. Series of N2O decomposition experiments were carried out using the catalysts. Cu/SBA-15 samples prepared by pH adjustment method showed higher catalytic activity thanCu-SBA-15 samples prepared by impregnation method.